Preface: 7th International Conference on Energy Material, Chemical Engineering and Mining Engineering (EMCEME 2025) - MacMillan, Sara; Dong, Fei (Transactions on Environment, Energy and Earth Sciences, 2026)
The 2025 7th International Conference on Energy Material, Chemical Engineering and Mining Engineering (EMCEME 2025), as an international forum aiming at presenting and exchanging technological advances and research results in the broad fields of energy material, environmentally friendly materials, chemical engineering, biological chemistry, resource exploration, and mining engineering, was held during December 27-28, 2025 in Zurich, Switzerland. EMCEME 2025 brought together leading researchers, engineers, and scientists in the domain of interest from around the world. During the conference, the participants shared their research results and discussed the development and research applications. Accepted papers after proper registration and presentation will be published into conference proceedings. Finally, we would like to express our gratitude to the reviewers of these manuscripts, who provided constructive criticism, stimulated comments, and suggestions to the authors. We are extremely grateful as organizers, technical program committee and editors, and extend our most sincere thanks to all the authors for their excellent contribution and work. EMCEME Organizing Committees Zurich, Switzerland